PENGARUH CITRA SEKOLAH TERHADAP KEPUTUSAN MEMILIH SEKOLAH PADA SISWA SMK KRISTEN 1 SURAKARTA - Wulan Merdeka Sari; Salman Alfarisy Totalia; Sudarno Sudarno (Department of Economics Education, Universitas Sebelas Maret, 2018)
The purposes of research was to find out: (1) whether or not there was an effect of product, price, place, promotion, people, physical evidence, process as main dimension of school image as simultaneously on the decision to choose the school at students of SMK Kristen 1 Surakarta (2) whether or not there was an effect of product, price, place, promotion, people, physical evidence, process as main dimension of school image as partially on the decision to choose the school at students of SMK Kristen 1 Surakarta. This research is quantitative research using descriptive methods and multiple regression analysis. Thepo pulation in this research is class X, XI and XII SMK Kristen 1 Surakarta amount to 449 students. The samples amount are 113 samples, respondent determination is by using nonprobability sampling that is proportionate stratified rando sampling. The data validity was obtained from the result of tryout conducted with 30 respondents. From the analysis results, regression equation is obtained, that is: Y= 3,597 + 0,465 X1 + 0,220 X2 + 0,017 X3 + 0,422 X4 + 0,074 X5 + 0,006 X6 + 0,558 X7. Seen from the result of F-test obtaining probability value of (0,000). It mean that there was a simultaneous effect of product, price, place, promotion, people, physical evidence, process as main dimension of school image on the decision to choose the school at students of SMK Kristen 1 Surakarta. The result of t-test on product variables obtaining probability values of (0,001) respectively, t-test on promotion variables values of (0,022) respectively, t-test on process variables values of (0,011) respectively. It meant that there was a partial effect of product, promotion, process variables on the decision to choose the school at students of SMK Kristen 1 Surakarta.